The effects of perceived service quality on patient satisfaction and behavioral compliance at a multi speciality public hospital in state of Pahang - Bahari, Mohamed (2015)
The quality of health care service is always at the forefront of professional, political, concern stakeholders, and managerial attention. However, the key dimensions contributing to health care service quality not been fully understood. Many studies have been conducted to measure health care service quality, but most of them in developed countries, especially in Europe and the USA; the results may not be applied to the Malaysian context due to difference in culture, environment, and facilities accessibility. Although, the health care service quality research in developing countries is growing nonetheless, the study is not widespread in Malaysia. Only few empirical studies on healthcare service quality from Malaysia can be identified published in journals and the findings are inconsistent. Thus, to fill this knowledge gap, this study developed a service quality model for health care service by framing the association of service quality antecedents, perceived service quality, patient satisfaction, and behavioral compliance. To validate the research model and test the proposed research hypotheses, the study used a quantitative approach as a research paradigm, cross-sectional design as a survey method, combination of cluster and convenience sampling as a sampling technique and partial least square structural equation modeling (PLS-SEM) as a data analysis technique. The findings of the study show that health care service quality is a context-specific and multi-dimensional constructs. Given the high power achieved from the analysis, this thesis has significant theoretical and practical contributions. Theoretically, the study extends service quality research by reconstructing the model as a reflective, multi-dimensional constructs and evaluating the impacts of antecedent constructs on perceived service quality, patient satisfaction and behavioral compliance in the context of health care service in Malaysia. Methodologically, the study validates that PLS-SEM is suitable to estimate the parameters of a multi-dimensional constructs. Practically, the study provides hospital management with a health care service quality model for conducting integrated analysis and design of service delivery systems. Overall, the study makes a significant contribution to healthcare organizations, better health outcomes for patients and better quality of life for the community